Recruitment of the cardiac conduction system for optimal resynchronization therapy in failing heart - Chen, Zhongli; Zhou, Xiaohong; Ma, Xuan; Chen, Keping (Frontiers in Physiology, 2022)
Heart failure (HF) is a leading health burden around the world. Although pharmacological development has dramatically advanced medication therapy in the field, hemodynamic disorders or mechanical desynchrony deteriorated by intra or interventricular conduction abnormalities remains a critical target beyond the scope of traditional medication treatment. In the past 2 decades, nonpharmacologic treatment for heart failure, such as cardiac resynchronization therapy (CRT) via biventricular pacing (BVP), has been playing an important role in improving the prognosis of heart failure. However, the response rate of BVP-CRT is variable, leaving one-third of patients not benefiting from the therapy as expected. Considering the non-physiological activation pattern of BVP-CRT, more efforts have been made to optimize resynchronization. The most extensively investigated approach is by stimulating the native conduction system, which is referred to as the His‑Purkinje conduction system pacing (CSP), including both the His bundle pacing (HBP) and the left bundle branch area pacing (LBBAP). These emerging CRT approaches provide an alternative to traditional BVP-CRT, with multiple proof-of-concept studies indicating the safety and efficacy of its utilization in dyssynchronous heart failure. In this article, we summarize the mechanisms of dyssynchronous HF mediated by conduction disturbance, the rationale and acute effect of CSP for CRT as well as the recent advancement in clinical research, and further discuss possible future directions of CSP.